Waste plastic- and coke-derived flash graphene as lubricant additives. (25th January 2023) - Advincula, Paul A.; Granja, Victoria; Wyss, Kevin M.; Algozeeb, Wala A.; Chen, Weiyin; Beckham, Jacob L.; Luong, Duy Xuan; Higgs, C. Fred; Tour, James M.
Abstract: Lubricants play an essential role in reducing wear in mechanical systems. Carbon nanomaterial additives, such as graphene, have been found to significantly improve tribological performance when used as lubricant additives. Here, post-consumer plastic and metallurgical coke are converted into turbostratic flash graphene (FG) through flash Joule heating (FJH). The FG is then added to either poly(alpha olefin) 6 or 9 (PAO 6 or PAO 9). Adding waste plastic-derived FG (WPFG) and metallurgical coke-derived FG (MCFG) to lubricants resulted in a significant decrease in the coefficient of friction (CoF), wear scar diameter (WSD), and roughness during four-ball testing. WPFG and MCFG decrease the CoF in PAO 9 by 6% and 9% at 0.1 mg mL −1, respectively, and in PAO 6 by 23% and 6% at 0.5 mg mL −1, respectively. WPFG and MCFG decrease the WSD of steel balls in PAO 9 by 14% and 8% at 0.5 mg mL −1, respectively, and in PAO 6 by 12% and 14% at 0.5 mg mL −1, respectively, by forming a coating-like layer between the metal surfaces. Roughness decreased by 38% and 32% for WPFG and MCFG in PAO 6, respectively, and by 35% and 29% for WPFG and MCFG in PAO 9, respectively. Finally, preliminary life cycle analyses demonstrate that production of FG produces up to 99% less greenhouse gas emissions, requires 98% less energy, and consumes 99.9% less water when compared to conventional production techniques of graphene. Hence, metallurgical coke and waste plastic are shown to be ready feedstocks for high-quality FG lubricant additives. Graphical abstract: Image 1